Artificial Intelligence Integration Strategy in Management Information Systems: A Case Study of Micro, Small, and Medium Enterprises - Emi Sita Eriana; Asep Erlan Maulana (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2026)
Digital transformation through the integration of Artificial Intelligence (AI) technology into Management Information Systems (MIS) has become an urgent need for Micro, Small, and Medium Enterprises (MSMEs). The MSME sector in Indonesia plays a vital role in the national economy but faces significant challenges, including limited access to capital and technology. This study aims to develop an effective AI integration strategy to improve MSME operational efficiency. Using a mixed-methods approach combining exploratory and descriptive designs, this study involved 30 MSMEs from various sectors selected through purposive sampling. Data were collected through structured questionnaires, semi-structured interviews, and direct observation, and then analyzed using descriptive statistics, regression analysis, and thematic analysis. The results reveal a paradox: 85% of MSMEs show strong enthusiasm for AI technology while simultaneously facing implementation barriers. A significant gap exists between infrastructure readiness (40%) and human resource readiness (25%). Five critical success factors were identified: human resource readiness (35%), technology infrastructure (25%), financial support (20%), management commitment (15%), and the digital ecosystem (5%). MSMEs that successfully implemented AI achieved operational efficiency improvements of up to 30% and ROI within 12–18 months. This study produced the